Recyclingplas VI Conference : plastics recycling as a future business opportunity, May 22-23, 1991, at the Mayflower Hotel, Washington, DC - RecyclingPlas Conference (6th : 1991 : Washington, DC); Plastics Institute of America, Inc. (Lancaster, PA : Technomic, 1991)
10